2018
DOI: 10.3758/s13428-018-1031-x
|View full text |Cite
|
Sign up to set email alerts
|

Direction dependence analysis: A framework to test the direction of effects in linear models with an implementation in SPSS

Abstract: In nonexperimental data, at least three possible explanations exist for the association of two variables x and y: (1) x is the cause of y, (2) y is the cause of x, or (3) an unmeasured confounder is present. Statistical tests that identify which of the three explanatory models fits best would be a useful adjunct to the use of theory alone. The present article introduces one such statistical method, direction dependence analysis (DDA), which assesses the relative plausibility of the three explanatory models on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 79 publications
1
31
0
1
Order By: Relevance
“…Compared with baseline, responses from timepoint 2 indicated that use of problem solving and use of social support as coping strategies were negative and positive predictors of traumatic stress, respectively (see Table 3 ). In order to further clarify the relationship between social support and traumatic stress, we employed DDA [ 15 ]. We hypothesized that greater traumatic stress would lead to more frequent use of social support seeking as a coping mechanism (IES-R €→ Social support), while controlling for gender, seniority, living arrangements, marital status, exposure to patients with respiratory symptoms, and deployment to high-risk areas (NCID).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with baseline, responses from timepoint 2 indicated that use of problem solving and use of social support as coping strategies were negative and positive predictors of traumatic stress, respectively (see Table 3 ). In order to further clarify the relationship between social support and traumatic stress, we employed DDA [ 15 ]. We hypothesized that greater traumatic stress would lead to more frequent use of social support seeking as a coping mechanism (IES-R €→ Social support), while controlling for gender, seniority, living arrangements, marital status, exposure to patients with respiratory symptoms, and deployment to high-risk areas (NCID).…”
Section: Resultsmentioning
confidence: 99%
“…We also employed linear regression analyses to examine the predictors of PSS, IES-R, and HWSS at each timepoint, while controlling for gender, seniority, marital status, living arrangement, exposure to patients with respiratory symptoms, and deployment to high-risk areas (NCID). Direction Dependence Analysis (DDA [ 15 ]) was then used to further clarify the direction of relationship between the predictors and outcome variables. DDA allows us to evaluate the theory of one-directional relationships between variables (e.g., x → y) as compared to other directional alternatives (e.g., y → x) using skewness and kurtosis of the data [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the approach presented here assumes that variables are nonnormally distributed. Higher-than-second moment information of variables has been used in the past in the development of causal discovery algorithms (Mooij, Peters, Janzing, Zscheischler, & Schölkopf, 2016;Shimizu, Hoyer, Hyvärinen, & Kerminen, 2006;Shimizu et al, 2011), confirmatory methods to test the direction of dependence in linear models (Wiedermann & Li, 2018;Wiedermann & von Eye, 2015), estimation algorithms in independent component analysis (Hyvärinen, Karhunen, & Oja, 2001), and search algorithms for covariate selection in linear models (Entner, Hoyer, & Spirtes, 2012). In the present study, we discuss similar principles for the development of unconfoundedness tests in mediation analysis and evaluate their performance in detecting potential confounders in mediator-outcome relations with randomized treatment.…”
mentioning
confidence: 99%
“…For example, the need to justify one’s effort, or to appear to oneself or the evaluator to have improved over time, could cause people to maximize the difference between posttest and retrospective pretest ratings when those rating scales are presented together. Statistical techniques such as stochastic frontier analyses (Rosenman et al, 2011) and directional dependence analysis (Pornprasertmanit & Little, 2012; von Eye & DeShon, 2012; Wiedermann & Li, 2018; Wiedermann & von Eye, 2015) provide methods to determine whether and to what degree such confounds are present at each measurement point.…”
Section: Common Mistakes and Pitfalls In The Literature About Retrospective Pretestsmentioning
confidence: 99%